Embedded Systems Design with FPGAs - Athanas, Peter.; Athanas, Peter.; Pnevmatikatos, Dionisios.; Pnevmatikatos, Dionisios.; Sklavos, Nicolas.; Sklavos, Nicolas. (Springer New York : Imprint: Springer, 2013)
This book presents methodologies for modern applications of embedded systems design, using field programmable gate array (FPGA) devices.  Coverage includes state-of-the-art research from academia and industry on a wide range of topics, including advanced electronic design automation (EDA), novel system architectures, embedded processors, arithmetic, dynamic reconfiguration and applications. Describes a variety of methodologies for modern embedded systems design;  Implements methodologies presented on FPGAs; Covers a wide variety of applications for reconfigurable embedded systems, including Bioinformatics, Communications and networking, Application acceleration, Medical solutions, Experiments for high energy physics, Astronomy, Aerospace, Biologically inspired systems and Computational fluid dynamics (CFD).